The Florida Panther: Past, Present, and Future - Madelon van de Kerk; Madan K. Oli; David P. Onorato (EDIS)
The Florida panther was presumed extinct by the early 1950s, but was rediscovered in 1973 by a survey team organized by the National Geographic Society. They were one of the first species to be added to the US endangered species list and are now the only population of North American puma that occurs east of Mississippi River. This 3-page fact sheet describes Florida panther research and management actions, the effects they have had on the population, and continuing challenges. Written by Madelon van de Kerk, David P. Onorato, and Madan K. Oli, and published by the UF Department of Wildlife Ecology and Conservation, February 2015.